PENGUNCI LOKER MENGGUNAKAN TOMBOL KEYPAD DENGAN KODE PASSWORD - , AHMAD SYIHAM DARWISY; , Nur Sulistyawati, S.T., M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Safety lockers with code keypad keypad password is a tool created to secure goods dismpan in it so that the stored goods is not taken by who is not its owner.This tool is divided into two parts, i.e. Part of the software and hardware. The Software used is the Bascom AVR and the Hardware that is used is the minimum system, atmega16, servo motor,LCD, keypad. The workings of this tool is the servo motor is used as Activator lever locks, servo opens a key lever if the password entered is correct and if it is wrong then the servo will not work. Password entered using the keypad LCD result is displayed. These lockers have four doors, each door has a different password and servo, for locking each door is also different.